Ambient Pressure Spectroscopy in Complex Chemical Environments - Head, Ashley R., editor 645664; Nemšák, Slavomír, editor 645665; Eren, Baran, editor 645666; ACS Publications (Online service) 645714 (Washington, DC : American Chemical Society, 2021)
Principles & Future of Next-Generation Spectroscopies. There has been an increasing rush of innovation in techniques to push the pressure limit higher in surface science experiments over the last twenty years. However, these new capabilities present practical difficulties in both performing the experiment and analyzing the data. This work explores the principles of vibrational, X-ray photoelectron, and X-ray absorption spectroscopies under ambient conditions and advanced applications of these techniques. Chapters on emerging techniques and instrumentation provide essential details of this new generation of spectroscopies.